Location, variations, and predictors of epicardial fat mapping using multidetector computed tomography to assist epicardial ventricular tachycardia ablation. Issue 10 (20th September 2017) - Sourwine, Mariaileen; Jeudy, Jean; Miller, Brian; Vunnam, Rama; Imanli, Hasan; Mesubi, Olurotimi; Etienne‐Mesubi, Martine; See, Vincent; Shorofsky, Stephen; Dickfeld, Timm
Abstract: Background: A significant number of ventricular tachycardia circuits are located close to the epicardial surface and are amendable to epicardial ablation. Epicardial fat often interferes with substrate mapping and ablation, though little is known regarding the distribution of fat and its fluctuation with the cardiac cycle. Methods: We studied 40 patients who underwent a 64‐slice multidetector computed tomography in order to describe patterns of epicardial fat distribution, variation during cardiac cycle, and clinical predictors of epicardial fat. Multiplanar reconstructions were analyzed during systole and diastole in six cross‐sections. Epicardial fat thickness was measured across multiple wall segments in each view. Results: Epicardial fat was found to be thicker in areas overlying coronary vasculature (7.8 ± 2.6 mm vs 3.5 ± 0.9 mm, P = 0.001), along with the right ventricular wall (3.9 ± 0.8 mm vs 2.6 ± 0.6 mm, P = 0.001) and the ventricular base (6.1 ± 1.7 mm vs 4.6 ± 1.6 mm, P < 0.01). Epicardial fat thickness increased 27% during systole as compared to diastole (4.9 ± 2.7 mm vs 6.2 ± 3.0 mm, P = 0.04). Variation with cardiac cycle was most evident along the right ventricular wall (3.9 ± 0.8 mm vs 5.0 ± 1.3 mm, P = 0.001) and nonvascular areas (P = 0.001), especially at the ventricular base (3.7 ± 1.1 mm vs 5.3 ± 1.5 mm, P = 0.001). In multivariate logistic regression, we found that age >50 years (P = 0.031) and coronary artery disease (P = 0.023) were statistically correlated with epicardial fat >5‐mm thickness and body mass index > 33 (P = 0.052) nearly so. Conclusions: Baseline epicardial fat thickness >5 mm is common in areas typically targeted during epicardial ablation and further increases during the cardiac cycle. Simple clinical characteristics can identify patients with >5 mm epicardial fat in which preprocedural computed tomography imaging and three‐dimensional fat map reconstruction may facilitate epicardial ablation.